Translations of proper names in two hugolian novels - Raková, Zuzana (Romanica Olomucensia, 2014)
The article discusses the problem of translation or non-translation of two main categories of proper names, anthroponyms and toponyms, found in a corpus composed of several Czech translations of two Hugolian novels, including Les Misérables and Notre-Dame de Paris. The aim of the study is to define the process used to translate anthroponyms and toponyms by different translators.
Keywords: translation; non-translation; report; phonetic assimilation; graphical assimilation; anthroponyms; toponyms.